Design of a Rice Drying System Prototype Based on PLC Simatic S7-1200 - Mochammad Machmud Rifadil; Suryono; Ferry Astika Saputra; Achmad Akhdanizar Rafli (Jurnal Serambi Engineering, 2026)
Rice drying in Indonesia generally still uses conventional methods by utilizing sunlight. However, weather changes often become obstacles, hampering the drying process. This research designed an automatic rice dryer based on PLC that uses PLN electricity as a power source and a heater as the heating element. The system is equipped with a sensor to monitor the moisture content of the rice so that the heater automatically turns off when the rice is dry. A DC motor is used as a drive to move the rice during the drying process. PLC programming is carried out using TIA Portal software with ladder diagram language. Based on testing for 33 minutes, the drying temperature increased from 30.7°C to 33.29°C, while the moisture content of the rice decreased from 21.20% to 13.54%, and the rice weight decreased from 1000g to 919g. These results indicate that the PLC-based drying system can control the rice drying process in a stable and effective manner. This tool is expected to be widely implemented on an agricultural scale to improve rice quality efficiently and reduce dependence on unpredictable weather conditions.